2011
DOI: 10.1017/s1368980011003193
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of self-reported weight and height in the Sister Study

Abstract: Objective To assess accuracy and reliability of self-reported weight and height and identify factors associated with reporting accuracy. Design Analysis of self-reported and measured weight and height from participants in the Sister Study (2003–2009), a nationwide cohort of 50,884 women aged 35–74 in the United States with a sister with breast cancer. Setting Weight and height were reported via computer-assisted telephone interview (CATI) and self-administered questionnaires, and measured by examiners. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
89
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 26 publications
7
89
3
Order By: Relevance
“…18 Post hoc tests indicated that seeing either label was associated with significantly reduced 19 consumption as overweight increased and with significantly reduced consumption in weight- 20 concerned participants of lowest SES. 21 These results provide some support for previous research finding paradoxical effects of 22 nutritional labelling. However, taking account of the behaviour of non weight concerned 23 eaters and those seeing different labels, it is apparent that this effect in those of higher SES 24 is a consequence of reduced consumption in non weight concerned eaters seeing a low fat 25 label rather than increased consumption in weight concerned eaters seeing the low fat label.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…18 Post hoc tests indicated that seeing either label was associated with significantly reduced 19 consumption as overweight increased and with significantly reduced consumption in weight- 20 concerned participants of lowest SES. 21 These results provide some support for previous research finding paradoxical effects of 22 nutritional labelling. However, taking account of the behaviour of non weight concerned 23 eaters and those seeing different labels, it is apparent that this effect in those of higher SES 24 is a consequence of reduced consumption in non weight concerned eaters seeing a low fat 25 label rather than increased consumption in weight concerned eaters seeing the low fat label.…”
supporting
confidence: 69%
“…Specifically, the data in Figure 1 suggested that, although there 20 was no moderating effect of BMI on the relationship between label and consumption, obese 21 participants seemed to eat less in response to seeing either a high or low fat label compared 22 to no label. The data in Figure 2 suggested that weight-concerned participants of lowest SES 23 seemed to eat less in response to seeing either a high or low fat label compared to no label.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The questionnaire inquiring about hardship has not been validated and could underestimate hardship exposure because of social stigma. We relied on self-reported prepregnancy weight, which may not be accurately reported; however, as we found and others have shown, [41][42][43] self-report tends to be highly correlated with measured weight, and thus ranking is likely to have been preserved across women. Furthermore, the prevalence of obesity, excessive GWG, and SPPWR were each similar to estimates from many other studies conducted around the same period.…”
Section: Discussionmentioning
confidence: 99%